2013
DOI: 10.4271/2013-01-1724
|View full text |Cite
|
Sign up to set email alerts
|

New Polymeric Coating on Sputtered Bearings for Heavy Duty Diesel Engines

Abstract: Worldwide emissions standards are becoming increasingly rigorous, and this leads to more complex engine demands. Several new PCU (Power Cell Unit) technologies are being applied to cope with these demands. This means engine parameters are changing, e.g. higher EGR (Exhaust Gas Recirculation) rates, higher PCP (Peak Cylinder Pressure), lower viscosity oils, higher oil contamination and soot. Therefore the operating conditions for the bearings have drastically changed, leading to an environment prone to seizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…have also reported that sputtered Al–Sn-based overlay coated with PAI-based overlay containing solid lubricants has better seizure performance compared to Al–Sn-based overlays without the polymer coating when tested in an intermittent lubricated condition. 21 B1 which is the conventional Pb-containing bearing material shows better seizure behaviour than the other test materials except the PAI-based overlay-coated material. The presence of Pb soft phase improves lubrication since there is formation of interfacial film when Pb is smeared.…”
Section: Resultsmentioning
confidence: 92%
“…have also reported that sputtered Al–Sn-based overlay coated with PAI-based overlay containing solid lubricants has better seizure performance compared to Al–Sn-based overlays without the polymer coating when tested in an intermittent lubricated condition. 21 B1 which is the conventional Pb-containing bearing material shows better seizure behaviour than the other test materials except the PAI-based overlay-coated material. The presence of Pb soft phase improves lubrication since there is formation of interfacial film when Pb is smeared.…”
Section: Resultsmentioning
confidence: 92%
“…Dimples on rings can also reduce friction [21,22]. Today, some engines are manufactured by mass production with laser dips along the liner [23] with different patterns (cf. Figure 15).…”
Section: Mesoscopic Levelmentioning
confidence: 99%
“…The properties of the surface material can be tailored to maximize performance depending on the application. [1][2][3] Fluid-film plain journal bearings are routinely analysed using elastohydrodynamic lubrication (EHL) methods. SABRE-TEHL is a software simulation tool used for performing thermo-elastohydrodynamic (TEHL) analysis of bearing applications.…”
Section: Introductionmentioning
confidence: 99%